POLA KOMUNIKASI LM WEDDING PLANNER & EVENT ORGANIZER DALAM MENJALIN RELASI BISNIS DENGAN VENDOR - Syifa'urrahmah, Angelia Devi; Surkadani, Puspita Sari (The Commercium, 2024)
This study aims to investigate the communication patterns of LM Wedding Planner & Event Organizer in establishing business relationships with vendors. The subjects of this study consist of six informants, including LM Wedding Planner & Event Organizer and vendors who have business collaborations, namely Laksmi Muslimah, Niko Eco Catering, Eden Design, as well as the two clients of LM Wedding Planner & Event Organizer. The researcher employed a qualitative method and analyzed the data using data reduction, data display, and conclusion drawing. The results indicate that the communication patterns within both the LM Wedding Planner & Event Organizer team and the vendors include formal communication patterns such as upward, downward, and horizontal. communication. Furthermore, LM Wedding Planner & Event Organizer uses an interactional business communication model to interact with vendors, while the vendors also use the same communication model, namely interactional business communication, to interact with LM Wedding Planner & Event Organizer.